Adsorption of platinum group elements (Pd(II), Ir(III) and Rh(III)) from aqueous solutions using 3-aminopropyl(diethoxy)methylsilane (APDEMS) functionalised bentonite. (January 2022) - Mosai, Alseno K.; Tutu, Hlanganani
Highlights: Bentonite was functionalised with 3-aminopropyl(diethoxy)methylsilane (APDEMS). Pd(II), Ir(III) and Rh(III) were recovered from aqueous solutions using the adsorbent. Maximum recovery of Ir(III) and Rh(III), was achieved at 10 g L -1, 2 mg L -1 and pH 2. Adsorption of Pd(II) was high (>98%) at all concentrations and pH with 5 g L -1. APDEMS-functionalised bentonite can be used to counteract the loss Pd, Ir and Rh. Abstract: The recovery of platinum group elements (PGEs) from waste is of high importance due to losses incurred during their processing, high input costs and diminishing primary resources. The recovery of Pd(II), Ir(III) and Rh(III) by bentonite functionalised with 3-aminopropyl(diethoxy)methylsilane (APDEMS) was investigated. Optimum conditions (adsorbent dosage, pH, concentration and competing ions) for the maximum uptake of PGEs by APDEMS-functionalised bentonite were determined. The maximum recovery of Ir(III) and Rh(III) was attained at pH 2, 10 g L -1 adsorbent dosage and 2 mg L -1 initial concentration. However, lower adsorbent dosage (5 g L -1 ) was required for maximum adsorption of Pd(II) at all concentrations. The adsorption efficiency of Ir(III) decreased significantly (p < 0.05) as pH increased, but was fairly constant for Pd(II) and Rh(III). The adsorbed amount of Ir(III) and Rh(III) increased when competing ions were incorporated. APDEMS-functionalised bentonite proved to be a potential adsorbent for effective recovery of Pd(II), Ir(III) and Rh(III) from mining and industrial wastewaters in order to curb the losses incurred during processing and application.